2017
DOI: 10.1039/c7ta03999a
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-enriched polydopamine analogue-derived defect-rich porous carbon as a bifunctional metal-free electrocatalyst for highly efficient overall water splitting

Abstract: A carbon-based, bifunctional metal-free water splitting electrocatalyst is prepared using a nitrogen-enriched polydopamine analogue to produce defect-rich porous carbon, which exhibits superb catalytic activities for both the HER and the OER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 60 publications
0
25
0
1
Order By: Relevance
“…Impressively, apart from tuning templates, a slight adjustment in carbon precursors can produce different features in the resulting hollow carbons. [ 152 ] For instance, uniform hollow carbon spheres with a smooth surface and SSA of 653 m 2 g −1 were prepared from pyrolysis of polydopamine‐coated SiO 2 nanospheres. By contrast, when changing polydopamine to N‐enriched dopamine analog, defect‐rich porous carbon spheres were produced with enlarged SSA (1811 m 2 g −1 ), rich pyridinic N and numerous meso/micropores (centered at 0.6–1 and 8 nm) on carbon sphere shells.…”
Section: Hierarchically Porous Carbon Nanostructurementioning
confidence: 99%
“…Impressively, apart from tuning templates, a slight adjustment in carbon precursors can produce different features in the resulting hollow carbons. [ 152 ] For instance, uniform hollow carbon spheres with a smooth surface and SSA of 653 m 2 g −1 were prepared from pyrolysis of polydopamine‐coated SiO 2 nanospheres. By contrast, when changing polydopamine to N‐enriched dopamine analog, defect‐rich porous carbon spheres were produced with enlarged SSA (1811 m 2 g −1 ), rich pyridinic N and numerous meso/micropores (centered at 0.6–1 and 8 nm) on carbon sphere shells.…”
Section: Hierarchically Porous Carbon Nanostructurementioning
confidence: 99%
“…This catalyst was also used for self-powered electrochemical water splitting (Fig. 8e-g) to demonstrate its great potential for practical applications [188].…”
Section: Carbon-based Metal-free Oer/her Bifunctional Catalysts For Wmentioning
confidence: 99%
“…The N-doped carbon-based electrocatalysts prepared by using CPT for 6 h and 4 h demonstrated impressive HER and OER activities, with the overpotentials of ~ 0.16 and ~ 0.48 V at 10 mA cm −2 , and Tafel slopes of 54.7 and 78.5 mV dec −1 in acidic media, respectively. Additionally, in two-electrode water system, the two N-doped carbon-based electrocatalysts by using CPT for 6 h and 4 h achieved the current density of 10 mA cm −2 with the minimum voltage of 1.82 V, which was smaller than porous carbon-based counterparts (~ 2.0 V) in 0.1 M KOH [117]. The tremendous overall water splitting activity of N-doped carbonbased electrocatalyst might be ascribed to the composition of functional groups attained by using CPT for different reaction time.…”
Section: D Porous Carbon-based Electrocatalysts For Overall Water Spmentioning
confidence: 93%
“…In this regard, a metal-free defect-rich porous carbon (DRPC) bifunctional electrocatalyst having a large surface area of 1811 m 2 g −1 was developed by polymerization reaction, followed by the pyrolysis of polymerized product at 900 °C to demonstrate the overall water splitting (Fig. 9a, b) [117]. It was revealed that the DRPC accompanied immense N-content of 9.3 at % and displayed excellent bifunctional catalytic performances in alkaline media for both HER and OER.…”
Section: D Porous Carbon-based Electrocatalysts For Overall Water Spmentioning
confidence: 99%